Prosesi Mandi Pengantin dalam Pernikahan Adat Masyarakat Banjar di Kecamatan Betara - Yosa Oktriwagi; Mutia Kahanna (Ethnography : Journal of Cultural Anthropology, 2025)
From the research entitled "Bridal Bathing Procession in Banjar Community in Betara District, West Tanjung Jabung Regency, Jambi Province" aims to describe the bridal bathing procession in Banjar community in Betara District. The type of data collection uses qualitative methods, with interview, observation and documentation techniques. Bridal bathing is one of the traditional ceremonies carried out before the wedding ceremony in Banjar community in Betara District. Bridal bathing is a tradition that must be carried out in the marriage process according to Banjar customary beliefs and beliefs. Bridal bathing aims to purify oneself as a whole, both physically and spiritually. Banjar people believe that the bride's face will be radiant for 40 days and kept away from disaster. The equipment for the bridal bathing procession is young areca nut shoots, 40 types of cakes, 4 yellow sugar cane stalks, yellow thread rope, yellow clothes, yellow shawls, long cloth, mirror, comb, powder, kohl, hair oil, candles, prayer water and yasin water. Bridal bathing until now, one of them in West Tanjung Jabung Regency still carries out bridal bathing as one of the traditional wedding processions.